Sustainability of Integrated Farming Between Robusta Coffee and Goat Livestock in Pupuan District, Tabanan Regency - Elizabeth, Putu Sweken; Budiasa, I Wayan; Suamba, I Ketut (JURNAL MANAJEMEN AGRIBISNIS; Vol 11 No 2 (2023): Jurnal Manajemen AgribisnisDO - 10.24843/JMA.2023.v11.i02.p03, 2024)
Purpose of this research was to analyze actual income, optimize income and analyze the sustainability of integrated farming between Robusta coffee and goat farming in Pupuan District, Tabanan Regency. Location of research was determined purposive with several considerations. The research sample was 30 farmers plus seven experts. Data collected using in-depth interviews, surveys with questionnaires, browsing through the internet, literature studies, farmers' notes and reports from related agencies. Data analysis using Gross Margin analysis, Linear Programming with the help of BLPX88 Software, Multidimensional Scaling (MDS) with RAP-Farm approach, and Participatory Prospective analysis. Based on the research results, it is known that the average actual income of farmers from integrated farming between Robusta coffee and goat livestock is Rp 19.179.508,00 a year or Rp 1.598.292,00 a month. Optimizing the income of all farmers with a cultivated land area of 23.01 ha, it is stated that farming is carried out optimally with a maximum income of IDR 492.081.500,00 a year. An increase of Rp 29.033.405,00 or 6.27% a year from the gross margin value of Rp 463,048,095.00 a year. The sustainability status of all dimensions is stated to be quite sustainable with an index value of 64.73. Based on the Participatory Prospective analysis, it is known that the factors that most influence on sustainability are altitude, farmer's education level, climate conditions, government policy, availability of production inputs, frequency of extension and training of farmers, farmer's knowledge, coordination with institutions/agencies, availability of production facilities, availability of farmer capital. It can be suggested that farmers' income needs to be increased again by using the right farming technology. To maximize farming income, farmers should use labor in families that are still large. It is necessary to increase the index value and status of sustainability in all dimensions through intervention on the most influential key factors.